2013
DOI: 10.1007/s11625-013-0239-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation options for marine industries and coastal communities using community structure and dynamics

Abstract: (2014) Adaptation options for marine industries and coastal communities using community structure and dynamics. Sustainability Science, 9 (3). pp. 247-261.http://researchrepository.murdoch.edu.au/20315Copyright © Springer Japan 2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Philip Island ¼ 18.7%, Tasmanian west coast ¼ 16.2%, Kangaroo Island and Tasmanian east coast ¼ 14%: Tourism Research Australia 2011). The GSR is therefore a major contributor to the socio-economic fabric of Australia and particularly that of regional coastal communities (Metcalf et al 2014).…”
Section: Ecosystem Services and The Economics Of The Gsrmentioning
confidence: 99%
“…Philip Island ¼ 18.7%, Tasmanian west coast ¼ 16.2%, Kangaroo Island and Tasmanian east coast ¼ 14%: Tourism Research Australia 2011). The GSR is therefore a major contributor to the socio-economic fabric of Australia and particularly that of regional coastal communities (Metcalf et al 2014).…”
Section: Ecosystem Services and The Economics Of The Gsrmentioning
confidence: 99%
“…Most of the restructuring of fleets within small coastal towns has been through planned adaptation such as industry buybacks or autonomous adaptation in response to localized declines in marine resources and has seen larger and more technologically efficient vessels move to larger centres for their fishing and related activities. Although declining participation in fishing in small coastal towns can affect population size and thus the demand for other services (e.g., school teachers, medical staff, banks), limited planned adaptation by coastal communities to consider either the consequences of such declines or the adaptation options available appears to have occurred (Metcalf et al ., ; Bradley et al ., ). As most management of our interactions with marine socio‐ecological systems involves at least some biological and economic objectives (and potentially also social and/or cultural objectives) particularly in relation to fisheries, it is important to understand the impact of climate change on meeting these multi‐domain objectives and vulnerability to change at the community level.…”
Section: System Feedbacks and Holistic Fisheries Practices In A Changmentioning
confidence: 99%
“…For example, issues such as population change and the impacts of the changing exchange rate of the Australian dollar affect the tourism industry. Aside from the direct climate impacts on community vulnerability, case study examples (Metcalf et al ., ) showed that a range of non‐climate stressors (Table ) also had cumulative or synergistic impacts. In fact, some of these non‐climate stressors impacted fishers’ acceptance of the climate change driver.…”
Section: Marine Socio‐ecological Systems: An Adaptation Blueprint Formentioning
confidence: 99%
“…Implementing effective adaptive management strategies for climate change in marine ecosystems, however, remains difficult for stakeholders, due to the time frames of action vs. response, the inhibitory nature of current socio-economic structures (which are averse to change) and the time required to conduct the extensive community consultation that is necessary (Manning, Lawrence, King, & Chapman, 2015;Salik, Jahangir, Zahdi, & Hasson, 2015). In addition, socio-economic frameworks operate primarily on qualitative data that is problematic to integrate robustly with the quantitative climate change evidence required for informed decision-making (Metcalf, van Putten, Frusher, Tull, & Marshall, 2013). The effective integration of qualitative and quantitative knowledge on marine socio-ecological systems is necessary for simplifying complex ecosystem dynamics into observable and measurable indicators that can be communicated and assessed by decision-makers for informed decision-making to occur (Murray, D'anna, & Macdonald, 2016).…”
Section: Introductionmentioning
confidence: 99%